Evaluation of physiological parameters and gaze behaviour of air pistol shooters related to performance outcomes - Güler, G.; Simsek, D.; Tuncer, S.; Mon-Lopez, D. (International Journal of Performance Analysis in Sport, 2024)
The objective of this study was to evaluate the physiological parameters and quiet eye (QE) of air pistol shooters in relation to performance outcomes. QE duration, skin conductance (SC), and heart rate (HR) were recorded for 20 shooters (10 novices and 10 intermediates) during shooting. All variables were examined according to the score and total shots. Physiological parameters were evaluated according to the shooting phases. Intermediate shooters exhibited significantly longer QE duration than novices (p < .001). There were no significant differences in QE duration and normalised SC according to the score and normalised SC between groups (p > .05). In SC, an increase in the preparation and resting phase and a decrease in the aiming phase were observed in both groups (p < .001). Intermediate shooters had lower HR than novices in all phases (p < .001). Additionally, more HR changes were detected in the intermediate shooters than in novices. HR of 10-score shots was lower than other shots (p < .05). Intermediate shooters exhibited longer QE duration than novices and they can decelerate their HR before shots. Coaches are recommended to incorporate exercises into training programmes that will enhance the visual focusing skills and reduce heart rate for novice shooters.